Video prompting procedures to teach science electronic journaling to students with intellectual disability: Leveraging students with disabilities' learning endeavors - Almumen, Huda A (Journal of intellectual disabilities, 2024)
The purpose of this research exploration was to investigate the impact of video prompting procedures on the acquisition of electronic journaling skill, and how to create and present scientific knowledge previously learned by students with intellectual disabilities. Using single-subject, multiple probe, and multiple baseline-design across four participants with moderate intellectual disabilities, results revealed that participants could increase their number of correct, completed steps for creating their electronic journals for the science classes. Results also showcased that participants had an opportunity to encounter the tablet-based, evidence-based instructional strategy to learn how to introduce their scientific pieces, talk about and communicate their ideas and thoughts. Implications for future research and practice were provided.